IMPLEMENTASI PRINSIP GOOD FAITH DALAM PUTUSAN PERMANENT COURT OF ARBITRATION OLEH CHINA PADA SENGKETA LAUT CHINA SELATAN - Azlia Amira Putri (BELLI AC PACIS (Jurnal Hukum Internasional), 2023)
This legal research aims to examine the implementation of the principle of good faith in the decision of the Permanent Court of Arbitration between the Philippines and China in the South China Sea Case as a disputed country. The verdict of the South China Sea dispute was issued in order to resolve the dispute between the two countries to achieve peace and certainty in the disputed South China Sea region, thus eliminating shared unrest. The type of research used in this study is normative in order to provide data related to the state of the south china sea that has been a problem for a long time, mainly due to territorial claims based on china's use of historical rights. According to this research it is known that China refusing to comply with the decision of the Permanent Court of Arbitration, they also continue to carry out some activities in an effort to maintain its existence and power in the South China Sea region. Hence, China is considered not to implement the principle of good faith.